Production system analysis and breeding practices of indigenous goats in North Wollo zone, Amhara region, Ethiopia - Yeshareg Taye; Mengistie Taye; Kefyalew Alemayehu; Zeleke Tesema (Journal of Applied Animal Research)
This study describes the goat production system and breeding practices in selected districts of North Wollo zone, Ethiopia. Data were collected from 180 respondents through a semi-structured questionnaire and group discussions. Descriptive and GLM procedures were employed for data analysis. A mixed crop-livestock production system was the main production system in the area. The mean number of goats per household is 9.66 and they are mainly kept for cash income and meat consumption. The flock structure of indigenous goats consisted of a large number of female goats. Natural pasture and crop residue were the major feed resources in the dry and wet seasons, with an overall mean of 37.53% and 54.26%, respectively. Feed shortage, diseases, and drought were the major constraints for goat production. Most goat owners (97.1%) practiced an uncontrolled mating system. Most farmers (88.93%) reported selecting breeding goats to be a parent for the next generation. Body conformation and coat colour were the preferred traits for the selection of goats. The current level of goat management and breeding methods would not significantly enhance goats’ productivity and profitability. Therefore, designing management and genetic improvement programmes would be vital to improving the productivity of indigenous goats.